The Effect of Virtual Reality on Anxiety and Pain in Pre-Anesthesia - Aura Jonathan Anbiya Putra Amatris; Supriyadi Supriyadi; Wahyu Riyaningrum; Marta Tania Gabriel Ching Cing (Jurnal Keperawatan Profesional, 2026)
Patients undergoing surgery often experience pre-anesthesia anxiety and pain, which can affect their physical and psychological readiness as well as the smoothness of the anesthesia process. This condition is still commonly found in regional hospitals, so there is a need for non-pharmacological interventions that are easy to implement, effective, and safe. This study aims to evaluate the effect of Virtual Reality (VR) therapy on anxiety and pain levels in pre-anesthesia patients at Dr. R. Goeteng Taroenadibrata Hospital in Purbalingga. The research design used was a quantitative quasi-experimental study with a pretest-posttest approach and a control group. The sample consisted of 50 pre-anesthesia patients divided into two groups: an intervention group and a control group, each with 25 respondents. Anxiety levels were measured using the Amsterdam Preoperative Anxiety and Information Scale (APAIS), while pain was measured using the Visual Analogue Scale (VAS). Data analysis was performed using the Wilcoxon test to see the differences before and after the intervention in each group, as well as the Mann–Whitney test to compare the differences between groups with a significance level of p < 0.05.  The results showed a significant decrease in anxiety and pain levels in the intervention group after VR therapy, as well as a significant difference between the intervention and control groups. This study concluded that VR therapy is effective in reducing anxiety and pain in pre-anesthesia patients and can be implemented in regional hospitals.